SIGNALING PATHWAYS REGULATED BY BRASSICACEAE EXTRACT INHIBIT THE FORMATION OF ADVANCED GLYCATED END PRODUCTS IN RAT BRAIN - Al-Malki, Abdulrahman L.; Barbour, Elie K.; Huwait, EA; Moselhy, Said S.; Saeed ALZahrani, Anas Hassan; Kumosani, Taha A. (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: The goal of this study was identification signaling molecules mediated the formation of AGEs in brain ofrats injected with CdCl2 and the role of camel whey proteins and Brassicaceae extract on formation of AGEs in brain.Methods: Ninety male rats were randomly grouped into five groups; Normal control (GpI) and the other rats (groupsII-V) were received a single dose of cadmium chloride i.p (5 μg/kg/b.w) for induction of neurodegeneration. Rats ingroups III-V were treated daily with whey protein (1g/kg b.w) or Brassicaceae extract (1mg/kg b.w) or combinedrespectively for 12 weeks.Results: It was found that whey protein combined with Brassicaceae extract prevented the formation of AGEs andenhance the antioxidant activity compared with untreated group (p <0.001). Serum tumor necrosis factor (TNF-α) andinterleukine (IL-6) levels were significantly decreased (p<0.01) in rats treated with whey protein and Brassicaceaeextract formation compared with untreated. The combined treatment showed a better impact than individual ones(p<0.001). The level of cAMP but not cGMP were lowered in combined treatment than individual (p<0.01).Conclusion, it can be postulated that Whey protein + Brassicaceae extract formation could have potential benefits inthe prevention of the onset and progression of neuropathy in patients.